PENGARUH BAHAN PENGENYAL KOMERSIAL FOOD GRADE DAN TEPUNG KORO PEDANG PRA GERMINASI TERHADAP PENINGKATAN KUALITAS TIWUL INSTAN TINGGI PROTEIN - Najmah Istikaanah; Munasib Munasib; Friska Citra Agustia (Jurnal Gizi dan Pangan Soedirman, 2021)
The aim of the research was to make high protein instant tiwul from mocaf which was substituted with jack bean flour and given a food grade commercial thickener to improve its sensory aspect. The study used a randomized block design. The factors studied were germination treatment on jack bean (G), without pre germination (G1) and with pre germination (G2); Proportion of mocaf: jack bean flour : tapioca (w/w) (F), P1 = 75:15:10, P2 = 70:20:10 and P3 = 65:25:10 and Addition of Commercial food grade thickening agent (w/w; % to flour weight) (K), K1 = 0.5%, K2 = 0.75% and K3 = 1.0%. The variables studied were physicochemical properties (moisture content, ash content, formol value, rehydration ability, for the best treatment, protein and fat content were tested) and sensory properties. Data were analyzed by F test (ANOVA) and continued with DMRT (Duncan Multiple Range Test). Based on the effectiveness index test, the best instant tiwul was G2P3K3 (with pre germination; proportion of mocaf-jack bean flour-tapioca w/w 65:25:10; commercial food grade thickening agent 1%). This instant tiwul has a water content of 4.39% wb; protein 7.05%db (6.74%wb), fat 6.39% db (6.11%wb), ash 0.98%db (0.93%wb) and carbohydrates (by difference) 85.54% db (81.78% wb), coefficient rehydration 3,67 and formol value 0,0383 ml NaOH 0,1N/g bk.